2008
DOI: 10.1007/s10800-008-9676-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrooxidation and inhibition of the antibacterial activity of oxytetracycline hydrochloride using a RuO2 electrode

Abstract: This work reports on the electrochemical oxidation of oxytetracycline hydrochloride (OTCH) [(4S, 4aS,5aS,6S,12aS)-4-dimethylamino-1,4,4a,5, 5a,6,11,12a-octahydro-3,6,10,12,12a-hexahydroxy-6-methyl-1,11-dioxonaphthacene-2-carboxamide] on a RuO 2 electrode (DSA Ò ) by cyclic voltammetry and electrolysis. The electrocatalytic efficiency of the electrode material was investigated as a function of different aqueous buffer solutions with pH values of 2.10 and 5.45 as supporting electrolytes. Spectrophotometric stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 41 publications
(43 reference statements)
0
12
0
4
Order By: Relevance
“…In a previous study Malpass et al (2006) demonstrated a dependency of atrazine electrochemical oxidation on the presence of FAC. Moreover, the pH will influence the active surface sites of MMO anodes as well as their redox properties, accelerating the direct electron transfer reactions (Rossi et al, 2009). On the other hand, only around 30e40% of 2,4-D, triclopyr and iopromide removal was observed under these conditions, while DEET could not be oxidized.…”
Section: à2mentioning
confidence: 99%
“…In a previous study Malpass et al (2006) demonstrated a dependency of atrazine electrochemical oxidation on the presence of FAC. Moreover, the pH will influence the active surface sites of MMO anodes as well as their redox properties, accelerating the direct electron transfer reactions (Rossi et al, 2009). On the other hand, only around 30e40% of 2,4-D, triclopyr and iopromide removal was observed under these conditions, while DEET could not be oxidized.…”
Section: à2mentioning
confidence: 99%
“…This behavior might be due to obstruction of the active sites in the DSA® surface for the oxygen and chlorine evolution reactions. Rossi et al [36] reported similar behavior for cyclic voltammetric analysis of the oxytetracycline hydrochloride (OTCH) in buffered solution using a RuO 2 electrode. For the authors, this behavior suggest the adsorption of organic films formed by dimmers/polymers or intermediate products from OTCH, which obstruct the active surface sites in the oxide electrode.…”
Section: Resultsmentioning
confidence: 85%
“…With a growth of population, intensive agriculture and industrialization, a very important role today is played by clean water recovery processes from wastewater for reuse by elimination of antibiotics from terrestrial and aqueous resources. Several studies on degradation of tetracycline, using different technologies were conducted: using activated sludge processes [9], TiO 2 nanopore arrays electrode [10], TiO 2 and ZnO aqueous suspensions were also used in the photocatalytic oxidation of tetracycline, under simulated solar light [11], photocatalysis of TC with C-N-S tridoped TiO 2 material [12], electron pulse radiolysis [14][15][16][17], using Pt plates as anode [14], with Ti/RuO 2 anode [15]. In this study, the electrochemical reactions followed pseudo-first order kinetics.…”
Section: Introductionmentioning
confidence: 99%